2011
DOI: 10.1158/1055-9965.epi-10-1262
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Epidermal Growth Factor Receptor Status, p16INK4A, and Outcome in Head and Neck Squamous Cell Carcinoma

Abstract: Background: Human papilloma virus (HPV) infection is a powerful prognostic biomarker in head and neck squamous cell carcinoma (HNSCC). Increased epidermal growth factor receptor (EGFR) gene copy number and protein expression have been reported to be negative predictors of outcome. This study examined the relationship between HPV status, EGFR gene copy number, EGFR protein expression, and clinical outcome in HNSCC patients treated with chemoradiation. Methods: HPV status was determined using p16I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 34 publications
(66 reference statements)
9
55
0
Order By: Relevance
“…This may be attributable to higher EGFR copy number in HPV-negative compared with HPV-positive tumors [33][34][35][36]. EGFR signaling results in activation of several downstream pathways that may affect transcription or translation of VEGF, including the Ras/MAPK, PI3 K/ Akt/mTOR, and STAT3 pathways [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributable to higher EGFR copy number in HPV-negative compared with HPV-positive tumors [33][34][35][36]. EGFR signaling results in activation of several downstream pathways that may affect transcription or translation of VEGF, including the Ras/MAPK, PI3 K/ Akt/mTOR, and STAT3 pathways [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…10,18,19 How HPV status aff ects the outlook of patients with recurrent or metastatic disease, or their response to treatment, is unknown. Some studies [20][21][22][23][24] have suggested interactions between HPV and the EGFR signalling pathway. Therefore, HPV status (as assessed by p16 immunohistochemistry of formalinfi xed paraffi n-embedded samples) might aff ect outcomes during anti-EGFR treatment.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR immunopositive cells are indicated with brown chromogen within the cell membrane and cytoplasm. Three red signals ( EGFR gene; 7p12) and one green signal (Chromosome 7; 7p11.1-q11.1) indicate an increased EGFR to CEP7 ratio ( EGFR to CEP7 ratio ≥222 26). …”
Section: Resultsmentioning
confidence: 99%